Hybrid joining of jacket structures for offshore wind turbines – Validation under static and dynamic loading at medium and large scale. (1st February 2022) - Albiez, M.; Damm, J.; Ummenhofer, T.; Ehard, H.; Schuler, C.; Kaufmann, M.; Vallée, T.; Myslicki, S.
Highlights: An adhesive manufacturing process for adhesively bonded K-joints is developed. The assembly of full-scale bonded jackets is detailed. Bonded K-joints are tested under quasi-static, creep and fatigue load. Influence of different adhesives on the load bearing behaviour is pointed out. Adhesivly bonded joining concept is validated by large scale tests. Abstract: The wind energy sector is constantly looking for improving the efficiency of their facilities, including on offshore locations. Part of that strategy is the demand for increasingly larger offshore structures. This cannot be met only by simply upscaling existing solutions, as there are several reasons that prevent such a simple approach. Often the connections are decisive for the dimensioning of the load bearing structures. Novel approaches, as the one this paper presents, are necessary. To allow for even larger structures, a novel hybrid joint, which combines adhesive bonding with welding, is presented. The first part of this paper fully addressed the requirements, and allowed to select two suitable adhesives significantly differing in strength by a ratio of 10:1, and stiffness by a ratio 50:1. Based thereupon, this paper first addresses the design, and the corresponding manufacturing concept, which were fully simulated numerically. Time and effort put into these preliminary steps proved crucial, as it allowed implementing changes and adaptations that otherwise would have hampered the project. Due to its nature, it largely reduces complex, labour, and cost intensive welding operations on the legs of the jacket structure, and substitutes them by relative simple, fast, and cost-effective adhesive bonding. The solution devised offers an alternative to the complex welding on the primary structural elements, resulting notch stresses, and associated local weakening. Thus, the innovative approach relocated the critical section of the joint well outside the former welding seams, and capacity of the hybrid joint is now limited by that of the tubular elements under static and fatigue loading. This was validated at medium size, with samples scaled down to 1:10, and large scale, at 1:5, respectively.